The Use of a Wiki to Facilitate Collaborative Learning in a South African Physiotherapy Department - M. Rowe (AOSIS, 2012)
The dominant form of teaching in higher education remains the lecture,even though evidence suggests that it alone is inadequate to facilitate the development ofthe higher order thinking skills required in clinical practice. The use of wikis may have a roleto play in facilitating collaborative learning practices that are important for professionaldevelopment. This descriptive survey evaluated the use of a wiki for a collaborative learningactivity within small groups of undergraduate physiotherapy students in a South Africanuniversity. Students participated in a wiki-based assignment and were then surveyedusing open- and closed-ended questions to determine their perceptions and experiences of the process. The results indicate thatalthough a wiki can be used to develop relevant content, there were significant challenges in its implementation. These included apoor understanding by students of how to work effectively in groups, a lack of physical and epistemological access to the internet,and the need for adequate preparation and support. Some features of the wiki were found to have an impact on the quality ofthe work produced, including the use of Discussion pages, peer review, and the public nature of the wiki. The conclusion is thatwikis may have a role to play in collaborative groupwork, but that that students need to be adequately prepared and supportedthroughout the process.